Re-Excision Rates in Breast-Conserving Surgery for Invasive Breast Cancer after Neoadjuvant Chemotherapy with and without the Use of a Radiopaque Tissue Transfer and X-ray System - Jamaris, Suniza; Akpolat-Basci, Leyla; Stephanou, Miltiades; Wetzig, Sarah; Cubuk, Yueksel; Gerharz, Johannes; Bittner, Ann-Kathrin; See, Mee Hoong; Liedtke, Cornelia; Kolberg, Hans-Christian (Karger Publishers, 2018)
Background: Significant re-excision rates in breast-conserving surgery (BCS) after neoadjuvant systemic chemotherapy may result from difficulties in defining the surgical target particularly in cases with excellent treatment response. Devices allowing an exact topographic localisation of the lesion in the resected tissue could reduce re-excision rates by optimising the intraoperative detection of involved margins. Methods: 80 patients with invasive breast cancer receiving BCS after neoadjuvant chemotherapy were included in this non-randomized case-control study. 40 patients with specimen radiography performed in a standard approach (control group) were compared to 40 patients with use of a radiopaque tissue transfer system (study group). Results: 19/80 (23.75%) patients required re-excision because of involved margins; among those, 14/40 (35%) were in the control group and 5/40 (12.5%) in the study group. The association between the use of the radiopaque tissue transfer system and the lower re-excision rate was statistically significant (p = 0.023). Conclusion: Our analysis provides a rationale for the routine use of a radiopaque tissue transfer system for specimen radiography in BCS after neoadjuvant chemotherapy for invasive breast cancer in order to reduce re-excision rates. © 2018 S. Karger AG, Basel. All rights reserved.